2017
DOI: 10.1186/s12929-017-0336-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of L-citrulline transport through blood-brain barrier in the brain capillary endothelial cell line (TR-BBB cells)

Abstract: Background L-Citrulline is a neutral amino acid and a major precursor of L-arginine in the nitric oxide (NO) cycle. Recently it has been reported that L-citrulline prevents neuronal cell death and protects cerebrovascular injury, therefore, L-citrulline may have a neuroprotective effect to improve cerebrovascular dysfunction. Therefore, we aimed to clarify the brain transport mechanism of L-citrulline through blood-brain barrier (BBB) using the conditionally immortalized rat brain capillary endothelial cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Indeed, CSF uric acid levels are inversely correlated with risk of developing Parkinson's disease, and administration of uric acid is neuroprotective [73][74][75]. Likewise, citrulline and riboflavin, whose levels were elevated in dKO CSF, are reported to prevent neuronal cell death [76], and protect tissue from oxidative injury [77], respectively. Conversely, diminished dKO CSF levels of the antioxidants carnosine, Nacetylcarnosine, homocarnosine, and anserine could predispose the dKO rats to increased risk of oxidative stress-induced neurological injury as supported by high levels of methionine sulfoxide, a marker of oxidative stress [36].…”
Section: Plos Onementioning
confidence: 99%
“…Indeed, CSF uric acid levels are inversely correlated with risk of developing Parkinson's disease, and administration of uric acid is neuroprotective [73][74][75]. Likewise, citrulline and riboflavin, whose levels were elevated in dKO CSF, are reported to prevent neuronal cell death [76], and protect tissue from oxidative injury [77], respectively. Conversely, diminished dKO CSF levels of the antioxidants carnosine, Nacetylcarnosine, homocarnosine, and anserine could predispose the dKO rats to increased risk of oxidative stress-induced neurological injury as supported by high levels of methionine sulfoxide, a marker of oxidative stress [36].…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, it seems unlikely that it would transport the large neutral amino acid citrulline. However, LAT4 is known to functionally interact with the basolateral obligatory exchangers LAT1/2 and y + LAT1/2, which are suggested citrulline transporters [ 8 , [47] , [48] , [49] ]. In the intestine, LAT2 and y + LAT1 are most abundant [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that there is a crucial connection between the motor neuron degeneration and the differential regulation of nitric oxide synthase (NOS) in amyotrophic lateral sclerosis (ALS) in which L-arginine was found to provide the neuroprotective effect [17]. L-citrulline, a major precursor of L-arginine, has shown protective role in various other conditions like cardiac dysfunction, sickle cell disease, hypertension, and CNS dysfunction [5,16]. The purpose of this study was to examine the alteration of the transport characteristics of L-citrulline in NSC-34 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…L-Citrulline also showed the protective effects in cerebrovascular injury and neuronal cell death thereby preventing the NOS dysfunction [15]. Hence, L-citrulline could provide a potential therapeutic strategy thereby maintaining the impaired arginine metabolism and deficiency, protein homeostasis, and controlling NO metabolism disorders [16].…”
Section: Introductionmentioning
confidence: 99%